An Overview of Postgraduate Education in Latin America and Other Countries of the World (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The globalization of academic training, the development of transversal competencies in the differentcountries of the world, the diversification and expansion of graduate programs in Latin America, theCaribbean and other regions of the world, reflect the academic movement of graduate students in thedifferent universities. Postgraduate training programs are instruments of the policy of the states of eachcountry and through this purpose universities train specialized professionals of high academic level inthe different faculties and academic schools that offer quality education in Latin America and theCaribbean, pointing out some of them in Brazil, Colombia, Argentina, Chile, Peru, etc. In Peru,postgraduate education has undergone some changes with respect to the framework of the newuniversity law N° 30220, Chapter 5, on the academic organization in art. 43, on postgraduate studieswith specializations, postgraduate diplomas, specialization masters and research or academic masters,and doctorates. Each university establishes the duration of postgraduate studies and the credits orweights of the subject and these are established according to the university law and its regulations.Private universities are also subject to the governing body, who must authorize the NationalSuperintendence of University Education (SUNEDU) to control and supervise the normal developmentand operation of such educational institution. This overview to the postgraduate studies in the countriesof Europe and Asia, in comparison with Latin America and the Caribbean, the academic level of theprofessional training of the postgraduate studies in these continents such as Europe and Asia are of thehighest level, likewise they grant scholarships to Latin Americans to improve and specialize in mastersand doctorates in various universities in Europe and Asia, where there are more than 14 countries thatgrant scholarships to make postgraduate studies in different specialties, then postgraduate studies(masters, doctorate and specializations) are increasingly strengthened in the scientific and technologicalresearch of university education in Latin America, the Caribbean and other regions of the world.